Assessment of Mycotoxin Exposure in a Rural County of Chile by Urinary Biomarker Determination - Claudia Foerster; Gisela Ríos-Gajardo; Patricia Gómez; Katherine Muñoz; Sandra Cortés; Carlos Maldonado; Catterina Ferreccio (Toxins, 2021)
Aflatoxin B1 (AFB1), ochratoxin A (OTA), zearalenone (ZEN), and deoxynivalenol (DON) are frequent mycotoxins that may cause carcinogenic, mutagenic, estrogenic, or gastrointestinal effects. The aim of this study was to assess the exposure to and risk from AFB1, OTA, ZEN, and DON in 172 participants of the Maule Cohort (MAUCO) by a biomarker analysis in urine and to associate their exposure with food consumption and occupation. Mycotoxins in the first morning urine were analyzed by solid-phase extraction and quantified by Ultra-High-Performance Liquid Chromatography with a mass–mass detector. Participants’ information regarding food consumption, occupation, and other characteristics was obtained from a baseline and 2-year follow-up survey of the cohort. The prevalence and mean levels of mycotoxins in the urine were as follows: DON 63%, 60.7 (±78.7) ng/mL; AFB1 8%, 0.3 (±0.3) ng/mL; α-zearalenol (α-ZEL) 4.1%, 41.8 (±115) ng/mL; β-ZEL 3.5%, 17.4 (±16.1) ng/mL; AFM1 2%, 1.8 (±1.0) ng/mL; OTA 0.6% (1/172), 1.3 ng/mL; and ZEN 0.6%, 1.1 ng/mL. These results were translated into exposures of DON, ZEN, and aflatoxins of public health concern. Participants who consumed coffee and pepper the day before had a significantly greater presence of DON (OR: 2.3, CI95 1.17–4.96) and total ZEL (OR: 14.7, CI95 3.1–81.0), respectively, in their urine. Additionally, we observed associations between the habitual consumption of beer and DON (OR: 2.89, CI95 1.39–6.42). Regarding the levels of mycotoxins and the amount of food consumed, we found correlations between DON and nuts (p = 0.003), total ZEL and cereals (p = 0.01), and aflatoxins with capsicum powder (p = 0.03) and walnuts (p = 0.03). Occupation did not show an association with the presence of mycotoxins in urine.